Conversion in the Process of Assimilation of Loan-Words - Galstyan, Anahit (Armenian Folia Anglistika, 2006)
Conversion is one of the most productive means of word-formation which has immensely contributed to the morphological assimilation of the words borrowed from French. On the other hand, conversion is the result of the assimilation of the loan-words form French and from other languages. As a result of the semantic, phonetic, morphological assimilation of the loan-words, Modern English abounds in the so-called converted pairs and converted triples which are viewed as false conversions.